2004
DOI: 10.1542/peds.2004-1159
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis of Early Adrenal Insufficiency to Prevent Bronchopulmonary Dysplasia: A Multicenter Trial

Abstract: Prophylaxis of early adrenal insufficiency did not improve survival without BPD in the overall study population; however, treatment of chorioamnionitis-exposed infants significantly decreased mortality and improved survival without BPD. Low-dose hydrocortisone therapy did not suppress adrenal function or compromise short-term growth. The combination of indomethacin and hydrocortisone should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
302
1
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(321 citation statements)
references
References 43 publications
11
302
1
7
Order By: Relevance
“…Previous reports on the incidence of SIP are based primarily on randomized controlled trials, which have recorded SIP as secondary outcomes not clearly defined prior to the beginning of the study. [7][8][9] This has the potential to introduce poststudy selection bias. The current analysis, which included occult perforations to the greatest extent possible and had definitions defined prior to data collection, may yield a more accurate estimate of SIP prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports on the incidence of SIP are based primarily on randomized controlled trials, which have recorded SIP as secondary outcomes not clearly defined prior to the beginning of the study. [7][8][9] This has the potential to introduce poststudy selection bias. The current analysis, which included occult perforations to the greatest extent possible and had definitions defined prior to data collection, may yield a more accurate estimate of SIP prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, two NICHD randomized controlled, multicenter trials involving EPS in ELBW infants have been halted by their safety review committees because of perforations in the treated cohorts. 7,8 Meta-analyses of relevant randomized trials have confirmed that EPS is a risk factor for SIP. 9,10 While our concept of SIP as a disease entity has evolved, there is still some lingering debate as to whether or not SIP can be accurately distinguished from necrotizing enterocolitis (NEC) by the clinician.…”
Section: Introductionmentioning
confidence: 98%
“…16 Despite the clinical bias that infection should severely compromise the fetus, preterm infants exposed to chorioamnionitis seldom are septic and may have decreased mortality, 13 which was, however, not confirmed in other trials. 14,15 Watterberg et al 17 correlated histological chorioamnionitis with the incidence of respiratory distress syndrome (RDS) and BPD in ventilated preterm babies. In patients from the 1990s they found that preterm infants had a lower incidence of RDS if they were antenatally exposed to chorioamnionitis.…”
Section: Antenatal Inflammationmentioning
confidence: 99%
“…It is important to note that hydrocortisone administration without indomethacin treatment does not appear to increase the incidence of isolated gastrointestinal perforations. 40 Finally, although high-dose and prolonged hydrocortisone exposure after the first postnatal weak does not appear to affect long-term neurodevelopment, 41 there are no data available on the long-term effects of early low-dose hydrocortisone on brain development. Therefore, until data on long-term neurodevelopment of low-dose and early hydrocortisone treatment become available, hydrocortisone should be used carefully in the immediate postnatal period in the VLBW neonate and its use should be restricted to cases with vasopressor resistance.…”
Section: Vasodilation and Hyperdynamic Myocardial Functionmentioning
confidence: 99%